IDENTIFIKASI STRATEGI GURU KELAS 2 DALAM MENGA-TASI KESULITAN MEMBACA PERMULAAN DI SDN SIDOHARJO 02 - Muhammad Ibrahim Rais; Mar’atul Faida; Meilan Tri wuryani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to identify the strategies used by second-grade teachers in overcoming early reading difficulties at SDN Sidoharjo 02 and to explore the challenges encountered in their implementation. The research arises from the low early reading ability among lower-grade elementary students. A qualitative descriptive approach with a case study method was employed. Data were collected through interviews, classroom observations, and documentation involving one teacher and ten second-grade students. Data analysis followed an interactive model through data reduction, presentation, and verification.The findings reveal that teachers apply several key strategies, including daily reading habituation, turn-taking and group reading, individual guidance, and collaboration with parents. These strategies effectively improve students’ fluency and letter recognition. However, teachers face challenges such as varying reading abilities among students, limited instructional time, insufficient learning media, and minimal parental involvement. The study highlights the importance of collaboration among teachers, schools, and families in fostering early literacy skills. The results contribute to strengthening collaborative-based reading instruction practices in elementary schools.